A New Identification Method for Bolt Looseness in Wind Turbine Towers. (7th July 2019) - Xianlong, He; Tianli, She
Abstract : Flange plates are key joining components used in wind turbine towers. Bolt looseness results in common fatigue damage in wind turbine towers. Detailed vibration tests were carried out on six wind turbine towers with loose bolts. First, the bolt looseness situation of each wind turbine tower was detected by the torque method. The vibration characteristics of each tower were then tested and analyzed in detail before maintenance. Finally, the vibration characteristics were tested and analyzed in detail after maintenance. The experimental data analysis shows that the first-order natural frequencies of the wind turbine towers before and after bolt maintenance do not change; the damping ratio does not change significantly; and the first-order vibration mode remains effectively unchanged. The phase difference between the upper and the lower plates of a flange has a significant and abrupt characteristic even when the bolt looseness ratio is 6%; however, the phase difference does not exhibit this characteristic after the flange bolts are retightened. The experimental results show that compared with other vibration characteristics, the first-order phase difference characteristic of wind turbine towers is more markedly affected by the looseness of the flange bolts; hence, this characteristic can be used as a diagnostic that reflects flange bolt looseness. Whether the flange bolts of a given tower require tightening can be identified based on whether the absolute value of the phase difference between the upper and lower plates of the flanges suddenly increases. This research result can provide a new method for the identification of bolt looseness in wind turbine towers.